Photoinduced Electron Transfer Involving a Naphthalimide Chromophore in Switchable and Flexible [2]Rotaxanes. Issue 2 (11th December 2019) - Colasson, Benoit; Credi, Alberto; Ventura, Barbara
Abstract: The interlocking of ring and axle molecular components in rotaxanes provides a way to combine chromophoric, electron‐donor and electron‐acceptor moieties in the same molecular entity, in order to reproduce the features of photosynthetic reaction centers. To this aim, the photoinduced electron transfer processes involving a 1, 8‐naphthalimide chromophore, embedded in several rotaxane‐based dyads, were investigated by steady‐state and time‐resolved absorption and luminescence spectroscopic experiments in the 300 fs–10 ns time window. Different rotaxanes built around the dialkylammonium/ dibenzo[24]crown‐8 ether supramolecular motif were designed and synthesized to decipher the relevance of key structural factors, such as the chemical deactivation of the ammonium‐crown ether recognition, the presence of a secondary site for the ring along the axle, and the covalent functionalization of the macrocycle with a phenothiazine electron donor. Indeed, the conformational freedom of these compounds gives rise to a rich dynamic behavior induced by light and may provide opportunities for investigating and understanding phenomena that take place in complex (bio)molecular architectures. Abstract : Electron traffic : Multiple light‐induced electron‐transfer processes are enabled by mechanically interlocking molecular components that comprise chromophoric, electron‐donor and electron‐acceptor units.